1991
DOI: 10.1128/jcm.29.1.70-75.1991
|View full text |Cite
|
Sign up to set email alerts
|

Binding of S protein by Neisseria gonorrhoeae and potential role in invasion

Abstract: An agglutination assay was used to examine the binding of purified human S protein (vitronectin, serum spreading factor) to 201 clinical isolates of Neisseria gonorrhoeae. Strains belonging to the protein IA serovars were significantly (P < 0.001) more reactive in agglutination tests with human S protein and were more serum resistant than strains belonging to the protein IB serovars. The strains from patients with disseminated infections belonged predominantly to the IA serovar (19 of 23) and, with the excepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…suggesting a direct interaction (Arko et al, 1991); this interaction is unlikely to involve Opc as N. gonorrhoeae do not express the protein. A more recent study described that the nVn was more effective than polymeric (activated) Vn in the indirect heparin-dependent N. gonorrhoeae binding to Vn through the expression of certain Opa adhesins.…”
Section: Haemostasis Vitronectin Activation and Its Harnessing By Mementioning
confidence: 98%
See 1 more Smart Citation
“…suggesting a direct interaction (Arko et al, 1991); this interaction is unlikely to involve Opc as N. gonorrhoeae do not express the protein. A more recent study described that the nVn was more effective than polymeric (activated) Vn in the indirect heparin-dependent N. gonorrhoeae binding to Vn through the expression of certain Opa adhesins.…”
Section: Haemostasis Vitronectin Activation and Its Harnessing By Mementioning
confidence: 98%
“…However, specific targeting of soluble aVn and importance in serum resistance has been less well recognized. Interestingly, early studies on Neisseria gonorrhoeae (Arko et al, 1991) suggested that aVn may be required for gonococcal Vn-mediated serum survival. Although the mechanism of Vn binding was not known, gonococcal attachment to Vn was not affected by heparin A and B. MAC deposition and serum survival of capsulate MC58 (A and B) or H44/76 MsfB16++Dopc (C and D) in 10% PHS supplemented as shown were determined as described in Experimental procedures.…”
Section: Haemostasis Vitronectin Activation and Its Harnessing By Mementioning
confidence: 99%
“…The majority of the DGI isolates (n = 35; 92%) were highly serum resistant together with their Vn-binding capacity in comparison with septic joint and CSF isolates. Intriguingly, Vn binding was suggested as the major factor in survival and serum resistance of DGI isolates of N. gonorrhoeae (Arko et al, 1991).…”
Section: Figmentioning
confidence: 99%
“…Vitronectin has previously been shown to interact with the surface of several bacterial species, including Escherichia coli, Staphylococcus aureus, streptococci, Pneumocystis carinii, and Neisseria meningitidis (7,15,16,32), and it has been shown to promote agglutination of gonococci (2). In N. meningitidis, the acquisition of vitronectin increases the adherence of this bacterium to human umbilical vein endothelial cells (32).…”
Section: Figmentioning
confidence: 99%